The growth of the Red Mullet (Mullus barbatus, L. 1758) during the first years of life in the Ligurian Sea (Mediterranean) - Florentino F.; Zamboni A.; Rossi M.; Relini G. (Dynamique des populations marines, 1998)
Trawl studies were carried out seasonally in the Ligurian Sea for studying the growth of Mullus barbatus during its first years of life. The mean length at age was obtained by using both indirect and direct methods. Growth rate shows a clear seasonal pattern with a decrease during the first winter and the second autumn-winter of life. Sagitta readings showed a well-defined 'hyaline ring' in a large group of recently recruited fish, which cannot have a yearly meaning. Generally from the third ring onward these are laid down mainly between winter and spring. Considering the difficulties in interpreting sagitta readings, the age groups were allocated on the basis of two criteria. The first criterion selects all fish whose sagitta shows hyaline rings. The second criterion isolates those presenting fully formed annuli in the otoliths. While there is a good agreement among methods for the evaluation of the mean length at one year, the simple counting of hyaline rings in otolith readings leads to the underestimation of length from year two onward.
Deuxième Réunion du Groupe de Travail DYNPOP, 1996/10/02-05, Genova (Italy)